2020
DOI: 10.35848/1347-4065/ab9a8a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hygrothermal stress on potential-induced degradation for homojunction and heterojunction crystalline Si photovoltaic modules

Abstract: The influences of both high-voltage stress and hygrothermal stress were studied for homojunction and heterojunction crystalline Si photovoltaic (PV) modules. In order to separately access the influence of these stresses, these PV modules were subjected to sequential tests with hygrothermal stress and high-voltage stress for various stress durations of each test. It was found that for p-type homojunction crystalline Si PV modules hygrothermal stress applied in advance considerably enhances potential-induced deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…In SHJ PV modules, corrosion‐type PID is the main PID mode. [ 40–43 ] It must also be emphasized that corrosion‐type PID is a Na‐related phenomenon. Section 6 specifically addresses corrosion‐type PID.…”
Section: Degradation In N‐type Pert Cell Modules: Examples Of Three Degradation Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…In SHJ PV modules, corrosion‐type PID is the main PID mode. [ 40–43 ] It must also be emphasized that corrosion‐type PID is a Na‐related phenomenon. Section 6 specifically addresses corrosion‐type PID.…”
Section: Degradation In N‐type Pert Cell Modules: Examples Of Three Degradation Mechanismsmentioning
confidence: 99%
“…[ 41 ] Actual PV systems are typically limited both by technology and by regulations to 1000 or 1500 V. For that reason, Na‐penetration‐type PID is not regarded as easily occurring in actual PV systems. However, Masuda et al [ 42 ] demonstrated that the PID in SHJ cell modules is accelerated considerably by moisture ingress. It is also possible that SHJ cells with damaged TCO layers are more susceptible to Na‐penetration‐type PID.…”
Section: Na‐penetration‐type Pidmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, UV irradiation accelerates degradation by hygrothermal stress (9), on the other hand, delays degradation by potential difference (10). It was also found that hygrothermal stress accelerates the degradation by potential difference (11). Figure 2 shows materials and components used in photovoltaic modules and also degradation factors.…”
Section: Introductionmentioning
confidence: 99%